A new species of the genus Takydromus (Squamata: Lacertidae) from Tianjingshan Forestry Station, northern Guangdong, China - Wang, Ying-Yong; Gong, Shi-Ping; Liu, Peng; Wang, Xin (Zootaxa, 2017)
Many early descriptions of species of the genus Takydromus were based on limited diagnostic characteristics. This has caused considerable challenges in accurate species identification, meaning that a number of cryptic species have been erroneously identified as known species, resulting in substantially underestimated species diversity. We have integrated evidence from morphology and DNA sequence data to describe a new species of the Asian Grass Lizard, Takydromus albomaculosus sp. nov., based on two specimens from Tianjingshan Forestry Station, Ruyuan County, Guangdong Province, China. The new species can be distinguished from other known Takydromus species by distinctive morphological differences and significant genetic divergence in the mitochondrial COI gene. Morphologically, the new species differs from the known 22 congeners in the following combination of characters: relatively large body size, SVL 70.9 mm in female, 65.5 mm in male; presence of three or four pairs of femoral pores and four pairs of chin-shields; supraoculars three, rarely four, the posterior loreal either in contact with the anteriormost supraocular or not; the presence of supraciliary granules; the presence of six rows of ventral scales, strongly keeled in the male, and smooth but with the outermost row keeled in the female; the presence of enlarged and keeled lateral scales in a row above the ventrals, but shorter than the ventrals; subdigital lamellae 23–24 under the fourth finger and 29–30 under the fourth toe; dorsal surface brown, ventral surface green, flank dark brown or brown black with several prominent white round spots; the presence of a pair of white longitudinal dorsolateral stripes and a pair of white longitudinal ventrolateral stripes. Takydromus albomaculosus sp. nov. represents the twenty-third species of this genus, of which six species occur in northern Guangdong, where the biodiversity level of Takydromus is the second highest in the world, just below that of Taiwan.